PKM PEMBUATAN EKADO UDANG DI DESA TAMANGAPA, KECAMATAN MA’RANG, KABUPATEN PANGKEP - Asni, Andi; Jamal, Muhammad; Ilmiah, Ilmiah; Kasmawati, Kasmawati; Hamsiah, Hamsiah (JURNAL PENGABDIAN MASYARAKAT KAUNIAH, 2023)
Processing of fishery products as one of the activities to increase community income. Diversification of processed shrimp products can not only be done at the industrial level, but can also be done on a household scale. Based on the foregoing, it is necessary to conduct training on techniques for processing fishery products, especially shrimp processing in coastal communities. The objectives of the activity include: 1) Providing knowledge of vannamei shrimp processing techniques in the form of shrimp Ekado products, business management management, product product marketing techniques. 2) Eligibility to run an Ekado Shrimp business. The Partnership Program (PKM) activity was held on Friday, November 18, 2022 at the Indonesian Muslim Uversitas Assisted Village, namely Tamangapa Village, Ma'rang District, Pangkep Regency, at the homes of group members. The activity approach method is a participatory method where partners are directly involved in the implementation of activities from preparation to the implementation of these activities. The implementation of the approach method is in the form of counseling and training or demonstration. The output of the activity is in the form of a product with the specifications processed shrimp in the form of Ekado shrimp can be adopted properly. The shrimp ekado product processing business is worthy of being developed into a sustainable home industry business.